Groundwater of South Asia (Springer Hydrogeology,, 2018)
This books presents recent findings from the South Asian region (SA), broadly including groundwater studies on (a) quantity, (b) exploration, (c) quality and pollution, (d) economics, management and policies, (e) groundwater and society, and (f) sustainable sources. It offers a compilation of compelling, authentic insights into groundwater scenarios throughout the water-stressed South Asia region. Comprising Afghanistan, Bangladesh, Bhutan, India, Myanmar, Nepal, Pakistan, and Sri Lanka, it is the most densely populated region in the world: It occupies approximately 4% of the global land area but supports more than 25% of the global population. The SA region now faces an acute shortage of fresh water due to a rapid rise in water demand and changes in societal water-use patterns. Combining essential advances and perspectives, this book offers a valuable resource for all scientists, planners and policymakers who are interested in understanding and developing the SA and other related areas.